Effect of Infectious Diseases Specialist Consultation on the Management and Outcome of Patients in a Public Sector Hospital - Shumaila Ismail, Farzana Batool, Danish Khowaja, Irfan Ahmed Shaikh, Sohaima Manzoor, Shameem Behram Khan, Azizullah Khan Dhiloo (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To assess the effect of infectious diseases specialist consultation on the management and outcome of patients in a public sector hospital. Materials and Methods: This was a prospective cohort study in which a total of 313 patients were enrolled. This study was conducted in Dr Ruth Km Pfau Civil Hospital Karachi. The study duration was 6 month from 1st January, 2023 to 30 June, 2023. Data were collected from the medicine, surgery and allied departments of Civil Hospital Karachi by the study investigators themselves. For statistical analysis we used SPSS Version 25. Results: We included a total of 313 patients in our study, with a mean age of 52.31±10.51 years and an average length of stay of 13.04±5.50. These patients were distributed across various departments, with 91 (29.1%) from medicine, 110 (35.1%) from surgery, and the remaining 112 (35.8%) from other allied departments. The majority of patients, 63 (20.1%), were diagnosed with bacteremia, while 52 (16.6%) had urine infections, and 56 (17.9%) experienced urinary tract infections (UTI). Other diagnoses included Ventilator-associated pneumonia/hospital-acquired pneumonia (17.9%), Mixed infections (3.2%), Necrotizing Fasciitis (11.2%), Peritonitis (9.6%), Pancreatitis (2.6%), Surgical Site Infections (SSI) (6.4%), Diabetic foot infections (4.5%), Osteomyelitis (4.8%), and Meningitis (3.2%) respectively. Patients were categorized based on the etiology of infection, revealing that 14 (4.5%) patients had unexplained fever. Additionally, malaria was found in 21 (6.7%) patients, Dengue in 32 (10.2%), Tuberculosis in 27 (8.6%), ATT-induced hepatitis in 9 (2.9%), Multidrug-Resistant Organisms (MDROs) in 148 (47.3%), Methicillin-resistant Staphylococcus aureus (MRSA) in 49 (15.7%), Fungal infections in 11 (3.5%), and Viral infections in 2 (0.6%). Regarding outcomes, 229 (73.2%) patients exhibited clearance of bacterial or fungal cultures, 13 (4.2%) showed no disability at the time of discharge, 229 (76.7%) demonstrated improvement in signs and symptoms, and mortality occurred in 1 (0.3%) patient. Conclusion: It was concluded that consulting with experts in infectious diseases has a major impact on patient management and results. Keywords: Infectious Disease specialist, management, consultation.